Beyond the tip of the iceberg: Adolescent weight development of women and men with features of binge eating disorder. (August 2018) - Mustelin, Linda; Kaprio, Jaakko; Keski-Rahkonen, Anna
Abstract: Objective: Binge eating disorder (BED) is a clinical eating disorder that is strongly and bidirectionally related to overweight and obesity. Little is known about how subclinical features of BED relate to weight development in adolescence and young adulthood. Method: Women (n = 2825) and men (n = 2423) from the community-based longitudinal FinnTwin16 cohort participated. Seven eating-related cognitions and behaviors similar to the defining features of BED were extracted from the Eating Disorder Inventory-2 and were assessed at a mean age of 24. We used linear mixed models to assess the association of features of BED with BMI trajectories across four waves of data collection (mean ages 16, 17, 18, and 24). Results: The number of features of BED at wave 4 (age 24) was significantly associated with BMI from age 16 years onwards. Those reporting more features of BED had gained more weight throughout adolescence and into their twenties. Conclusions: Features of BED in young adulthood were preceded by steeper BMI trajectories in adolescence. A higher number of features were consistently associated with higher BMI and more weight gain. Highlights: We studied in a community sample how features of binge eating disorder (BED) relate to weight development in adolescence and early adulthood. Features of BED in early adulthood were preceded by steeper weight trajectories in adolescence. The more BED features the individuals reported as young adults, the steeper were their adolescent BMI trajectories.